Advanced exploitation of hagh-tin bronze alloys at medieval settlement Talgar in Kazakhstan - Park, S.; Savelieva, T. V. (НАРОДЫ И РЕЛИГИИ ЕВРАЗИИ, 2024)
A collection of bronze artifacts, including a mirror, round plate, thick-walled container, two thick-walled bowls, a thin-walled pot, two thin-walled bowls, a dish, and a strainer, retrieved from a medieval settlement in Talgar, Kazakhstan, underwent metallographic analysis. Typological dating places these objects within the 11th to 13th centuries AD. The examination revealed the use of high-tin bronze in various household items requiring advanced functionality. Two primary techniques were identified: 1) the use of high-tin bronze alloys as spacers and binders in creating double-walled containers for enhanced thermal insulation, and 2) the application of optimized thermo-mechanical treatments within the a+в phase field of the copper-tin phase diagram to enhance impact resistance. Additionally, the presence of zinc, tin, and lead hints at an ongoing transition from bronze to brass within the Talgar region during this period. Our investigation delved into the specific engineering processes employed and the level of technological sophistication evident in the production of these artifacts.